Kinetic and docking study of synthesis of glyceryl monostearate by immobilized lipase in non-aqueous media - Priyanka V. Jawale (11803674); Bhalchandra M. Bhanage (1392865) (2021)
Glyceryl monostearate is extensively used as an emulsifier in many industries. Mono acylation of glycerol was carried out by utilizing immobilized Candida antarctica lipase B (Cal B) as a biocatalyst and vinyl stearate as an acyl donor. Different reaction parameters, such as selection of lipases from various sources (like Candida antarctica , Candida rugosa, and Mucor meihei ) and their quantity, shaking speed, temperature, substrate concentration, and reusability were studied in detail to achieve excellent conversion. Overall, 98% conversion of glycerol was obtained at a mole ratio of 1:1 of glycerol to vinyl stearate, using 12 mg of immobilized Cal B at 45 °C for 3 h. The mechanism of the given reaction was anticipated based on the results of the Lineweaver-Burk plots. It was found that the reaction followed the Ping-Pong Bi Bi mechanism with inhibition of glycerol. As it was a kinetically controlled synthesis, different kinetic constants were estimated by non-linear regression analysis. The activation energy for Cal B was found to be 10.3 kcal/mol. Further, biocatalyst can be reused up to four catalytic cycles with an average four percent loss of activity. A molecular docking study was done to find out the confirmation of substrates and their binding positions in an enzyme. It was noticed that the reaction proceeds through acyl-enzyme complex formation followed by the transfer of that acyl group to another substrate.